4, 4′‐Diaponeurosporene‐Producing Bacillus subtilis Promotes the Development of the Mucosal Immune System of the Piglet Gut. Issue 10 (22nd March 2019) - Jing, Yuchao; Liu, Haofei; Xu, Wenwen; Yang, Qian
ABSTRACT: Gut mucosal immune responses are known to act as the first line of defense against invasion of pathogenic microorganisms. Piglets have an incompletely developed gut mucosal immune system, making them sensitive to intestinal infections. Promoting the development of the mucosal immune system will increase the pathogen resistance of piglets. The aim of the present study was to investigate the effect of carotenoid (4, 4′‐diaponeurosporene)‐producing Bacillus subtilis ( B.s ‐Dia) on intestinal mucosal immunity in piglets. We showed that oral administration to piglets of B.s ‐Dia remarkably improved the development of Peyer's patches (PPs) ( P  < 0.01), and increased villus height ( P  < 0.01) and colon crypt depth ( P  < 0.01). In addition, B.s ‐Dia also increased the number of intraepithelial lymphocytes ( P  < 0.01), while Bacillus subtilis ( B.s ) had no significant influence on it ( P  > 0.05). Moreover, B.s ‐Dia also increased the number of SIgA + cells ( P  < 0.01). Oral administration of either B.s or B.s ‐Dia increased the number of CD4 + and CD8 + cells in ileum lamina propria ( P  < 0.01). These results indicate that B.s ‐Dia contributes to a higher extent to porcine mucosal immune system development than B.s, and might serve as an immunopotentiator candidate. Anat Rec, 302:1800–1807, 2019. © 2019 American Association for Anatomy